SOCIALLY-ORIENTED APPROACH TO EDUCATION AS A CONDITION OF SUCCESSFUL SOCIALIZATION OF PUPILS - G. F. Trubina; E. F. Zeer; M. V. Mashchenko (Russian State Vocational Pedagogical University, 2017)
Introduction. The modern schools continue to focus on the individual achievements of students, which has led to inconsistency in the formation of personality, its social immaturity. As a result, it has become necessary to make an orientation of education not only to the development of the specific personality of a learner but also to the needs of the society surrounding the person, i.e. shifting the focus from student-centered approach to education of socially-oriented person.The aim of the publication is to present the concept of socially-oriented approach in education, which is a necessary condition for successful socialization of pupils.Methodology and research methods. The research is carried out with a support on pedagogical aspect of socialization; theory of professional self-determination of a personality; theory of synthesis of personal-oriented and socially-oriented approaches. Domain approach is applied to the description of the concept of socially-oriented education that is considered to have extensional, nonlinear, and multidimensional character. Analysis, synthesis, systematization and generalization of foreign and domestic scientific experience, modeling are used as the main methods of the research.Results and scientific novelty. The ideas of socially-oriented training and education which are available in domestic and foreign pedagogics are systematized. As a result of application of this approach, the concepts of socially-oriented approach to education and a socially-oriented personality are specified. The relevance of use of a new approach in education is proved; features of this approach are shown as methodological and methodical tools of educational activity wherein interests of society and a person as a subject of society are counterbalanced. The basic principles of socially-oriented approach are allocated and described; conditions of its realization at all educational levels are specified. As it is emphasized, one of the main and indispensable conditions of effective use of socially-oriented approach to education is creation of open spontaneous social and professional space which provides motivation of educational and work activities, getting a prestigious demanded profession, gaining self-development and professional growth.Practical significance. Methodological support for successful socialization of students in the learning process at all levels of school education is provided.